2011
DOI: 10.1093/infdis/jir121
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Is Detected Frequently in Stillbirths and Is Associated With Fetal Thrombotic Vasculopathy

Abstract: Stillbirth has multiple etiologies. However, the detection of CMV DNA in 15% of fetal tissues or placentae suggests a strong association between CMV infection in pregnancy and stillbirth. Molecular testing during postmortem investigation has an important role to determine the contribution of CMV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 39 publications
1
82
1
2
Order By: Relevance
“…CMV is known to infect placental tissues, but it is not known whether CMVdriven placental inflammation commonly triggers preterm labor, resulting in a correspondingly high incidence of congenital infection in preterm infants. 18 CMV-mediated hearing loss might be exacerbated by the ototoxic antibiotics and diuretics frequently used in intensive care. CMV-mediated thrombocytopenia and neutropenia might be expected to increase rates of IVH and sepsis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CMV is known to infect placental tissues, but it is not known whether CMVdriven placental inflammation commonly triggers preterm labor, resulting in a correspondingly high incidence of congenital infection in preterm infants. 18 CMV-mediated hearing loss might be exacerbated by the ototoxic antibiotics and diuretics frequently used in intensive care. CMV-mediated thrombocytopenia and neutropenia might be expected to increase rates of IVH and sepsis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, increasing evidence indicates that fetal injury can result from indirect effects through placental infection and placental dysfunction. 27,[35][36][37] CMV is now the leading nongenetic cause of congenital malformation in developed countries. 13 Despite this, the extent of the problem with cCMV infection is largely unrecognized by mothers, fathers, obstetricians, midwives, paediatricians, medical students and other clinicians.…”
Section: Congenital CMV Transmission and Diseasementioning
confidence: 99%
“…There is emerging evidence that viruses cause some stillbirths. Iwasenko et al reported that the detection of CMV DNA in 15 % of fetal tissue or placenta from 130 stillbirths [9].…”
Section: Pathogenesis Of Congenital CMV Infectionmentioning
confidence: 99%